Combattre pour la santé L'Armée d'Orient et la construction du système sanitaire grec, 1912-1922 - Korma, Léna (Bibliothèque des Écoles françaises d'Athènes et de Rome (BEFAR), 2022)
At the start of the 20th century, the upheaval in civil societies that were confronted with the shock of European armies led to a change in public health policy. In Greece, the Balkan wars, the First World War and the Greco-Turkish War brought ten years of conflict (1912-1922) during which movements of troops and refugees and a generally distressed population provided fertile ground for devastating epidemics. For the first time ever, this health, social and demographic crisis led to the advent of pro-active medical and social policies, based on late 19th century research into public health. Even though, at the time, the policies achieved little in concrete terms, they nevertheless set down the administrative, organisational and ideological foundations of the modern health system. This publication undertakes a study of this process through the influence of the French military mission and that of the Armée d'Orient, highlighting the complex interaction of the Greek and foreign actors involved in this "total war".